Larger deep white matter hyperintensity volume correlates with more severe social behavioral changes in patients with subacute ischemic stroke - Qu, Jian-Feng; Hu, Hui-Hong; Liu, Jian-Fei; Zhou, Yue-Qiong; Cheng, Wei-Yang; Shi, Lin; Luo, Yi-Shan; Zhao, Lei; Chen, Yang-Kun (Frontiers in Aging Neuroscience, 2023)
Background: Changes in social behavior can occur after ischemic stroke. We aimed to investigate the potential correlations between neuroimaging variables and changes in social behavior in patients who experienced subacute ischemic stroke. Methods: We prospectively screened patients with first-ever ischemic stroke. Three months after the index stroke, changes in patients’ social behavior were investigated by the Frontal Behavioral Inventory (FBI), which consists of both deficit and positive groups of behaviors. The protocol of brain magnetic resonance imaging (MRI) including the baseline MRI at the acute stage and additional MRI with three-dimensional T1-weighted imaging on follow-up. Using these MRI scans, we assessed the acute infarction and the volumes of various brain structures by an automatic volumetry tool. Results: Eighty patients were enrolled. In univariate analyses, patients with deficit behavioral changes had more left cortical infarction (r=0.271, P=0.015), Cholinergic Pathways Hyperintensities Scale scores (r=0.227, P=0.042), DWMH volumes (r=0.349, P=0.001), and modified Rankin Scale (mRS) scores (r=0.392, P<0.001). Patients with positive behavioral changes had more frequency of men (r=0.229, P=0.041) and a history of hypertension (r=0.245, P=0.028). In multiple stepwise linear regression models, after adjusting for age, deep WMH volumes (β=0.849, 95% confidence interval=0.352–1.346, P=0.001) and mRS scores on follow-up (β=1.821, 95% confidence interval=0.881–2.76, P<0.001) were significantly correlated with deficit behavioral changes (R2=0.245). Conclusion: Larger deep WMH volumes and poorer mRS scores on follow-up were significantly correlated with deficit behavioral changes in patients with subacute ischemic stroke.